Lithuanian undergraduate students' approaches to learning English for Specific Purposes - Burkšaitienė, Nijolė; Šliogerienė, Jolita (Journal of Education Culture and Society, 2021)
Aim. It has been established by research that the nature of students’ learning is closely related to their approach to learning and to the learning environment in which learning occurs. In higher education environments, students’ approaches to learning have been widely investigated across different fields of study, however, little known research has focused on students’ approaches to learning foreign languages. To contribute to knowledge in this field, the present research aims to establish undergraduate students’ approaches to learning English for Specific purposes (ESP) at a university in Lithuania.Method. The research was conducted with the participation of 111 undergraduate students, majors in 11 different study programmes, who took a mandatory course in ESP. The data were collected from the structured questionnaires; to carry out the research, quantitative methodology was used.Results.  The analysis of students’ engagement in the study activities, their willingness to go beyond the task and their ability to self-regulate their learning revealed that the study participants demonstrated both surface approach and deep approach to learning ESP.Conclusion. The results indicate that to guide the students towards deep approach to learning ESP at the university, their engagement in study activities should be fostered.